Alpha-Melanocyte–Stimulating Hormone Suppresses Oxidative Stress through a p53-Mediated Signaling Pathway in Human Melanocytes - Kadekaro, Ana Luisa; Chen, Juping; Yang, Jennifer; Chen, Shuna; Jameson, Joshua; Swope, Viki B.; Cheng, Tan; Kadakia, Madhavi; Abdel-Malek, Zalfa (Molecular cancer research, 2012)
Epidermal melanocytes are skin cells specialized in melanin production. Activation of the melanocortin 1 receptor (MC1R) on melanocytes by α-melanocyte–stimulating hormone (α-MSH) induces synthesis of the brown/black pigment eumelanin that confers photoprotection from solar UV radiation (UVR). Contrary to keratinocytes, melanocytes are slow proliferating cells that persist in the skin for decades, in an environment with high levels of UVR-induced reactive oxygen species (ROS). We previously reported that in addition to its role in pigmentation, α-MSH also reduces oxidative stress and enhances the repair of DNA photoproducts in melanocytes, independent of melanin synthesis. Given the significance of ROS in carcinogenesis, here we investigated the mechanisms by which α-MSH exerts antioxidant effects in melanocytes. We show that activation of the MC1R by α-MSH contributes to phosphorylation of p53 on serine 15, a known requirement for stabilization and activation of p53, a major sensor of DNA damage. This effect is mediated by the cAMP/PKA pathway and by the activation of phosphoinositide 3-kinase (PI3K) ATR and DNA protein kinase (DNA-PK). α-MSH increases the levels of 8-oxoguanine DNA glycosylase (OGG1) and apurinic apyrimidinic endonuclease 1 (APE-1/Ref-1), enzymes essential for base excision repair. Nutlin-3, an HDM2 inhibitor, mimicked the effects of α-MSH resulting in reduced phosphorylation of H2AX (γ-H2AX), a marker of DNA damage. Conversely, the p53 inhibitor pifithrin-α or silencing of p53 abolished the effects of α-MSH and augmented oxidative stress. These results show that p53 is an important target of the downstream MC1R signaling that reduces oxidative stress and possibly malignant transformation of melanocytes. Mol Cancer Res; 10(6); 778–86. ©2012 AACR.